Multi-faceted examination of a deepwater seamount reveals ecological patterns among coral and sponge communities in the equatorial Pacific - Brian RC Kennedy; Steven Auscavitch; Timothy M. Shank; Constance Sartor; Anameere Tennaba; Alexis M. Weinnig; Randi D. Rotjan (Scientific Reports)
Abstract Spatial changes in benthic community structure have been observed across natural gradients in deep-sea ecosystems, but these patterns remain under-sampled on seamounts. Here, we identify the spatial composition and distribution of coral and sponge taxa on four sides of a single central Pacific equatorial “model” seamount within the US EEZ surrounding the Howland and Baker unit of the Pacific Islands Heritage Marine National Monument. This seamount rises from 5,000 + m to mesophotic depths of 196 m, and is influenced by the Equatorial Undercurrent. Four remotely operated vehicle (ROV) transects were completed, one on each flank of the seamount. Shallower than ~ 250 m, the mesophotic seafloor was composed of scoured carbonate pavement with sediment accumulation only found in rocky depressions. Waters below 500 m hosted communities predominantly composed of octocorals, however, several coral taxa showed seamount flank preference (higher abundance on one or more flanks than the others) even though strong vertical (depth) zonation of corals and sponges was observed on all flanks. Euplectellidae, Plexauridae and ​​Chrysogorgia spp. corals each showed a distinct preference for flank. To help visualize the influence of current flow, oxygen, depth, and substrate type on the zonation of seamounts, we created an Alexander Von Humboldt-style infographic to illustrate the observed biodiversity patterns. Given the importance of seamounts to ocean biodiversity and productivity, this study is an early attempt at a holistic visualization of seamount biology that can advance new hypotheses about seamount ecology.